Bilateral Transposition Of Maxillary Canines And First Premolars : Orthodontic Management. A Case Report - Tan, Christopher Lawrence; Wong, Xian Hui (IIUM Medical Journal Malaysia, 2017)
Introduction: Transposition is a rare dental anomaly in positional interchange between two adjacent teeth. Studies indicated that tooth transpositions are more frequent unilateral than bilateral (12:1). It is a very rare phenomenon when the anomaly is bilateral and affects same teeth on both sides. The case of a 17 year old girl, with class I incisor relationship on class 1 skeletal base with bilateral transposition of maxillary canines-first premolars, severe crowding and posterior crossbite, is presented. This case report demonstrates the orthodontic management of bilateral transposition of maxillary canines-first premolars and by the end of treatment, the transpositions were maintained while achieving a good functional and aesthetic result.